Web-Based Learning Media Information System Case Study Of 05 Tebat Karai State Elemehntary School - Pero Alfian; Gunawan Gunawan; Sri Handayani; Marissa Utami (Penerbit Jurnal Indonesia, 2023)
In the implementation of the teaching and learning procces teachers must be able to make efforts to improve student achievement. One way that can be done by a teacher to motivate student in teaching is with learning media. Teachers also have to know how to make students confortable in learning and not boring. Teachers can use interesting web media anad can make students happy to learn. This study aims to describe the results of developing web-besed learning media for Sd Negeri 05 Tebat Karai and examine the effectiveness of the results of developing web-besed learning media. Research development is a procces or steps to develop a new product or improve an existing product and can be accounted for. This rearch was conducted design (before-after). This media received a good qualification asssement, because based on the validation results obtained scores from subject matter experts and from tests from media experts got scores. So, the web-based learning media that has been developed can improve student learning outcomes and is suitable for use as a learning medium for Sd Negeri 05 Tebat Karai. Based on the results of development research, it was concluded that this study produced an interesting and easy-to-use product in learning in the form of a web-based learning media for Sd Negeri 05 Tebat Karai that had been tested and declared valid and could be used for learning.